Chemical and Sensory Properties of Instant Coffee from Argopuro Regency - Rosdiana, Eva; Kusumaningtyas, Rizky Nirmala; Pratita, Dian Galuh (P3M Politeknik Negeri Jember, 2024)
Instant coffee was one of diversification product from ground coffee. This product was popular and consumed by many people because of the reason liked easily to make, more efficient, didn’t have pulp and soluble in water. The study aims to determine chemical properties and quality sensor of instant coffee from Argopuro regency. Co- crystallization was the method that used to make coffee instant product. The crystallization agent that commonly used is sucrose from sugar. The process occurred when the sucrose concentration in the solution was at a super saturated level, it would make coating compound molecules in the form of crystal nuclei and grew into larger component. This study used a Randomized Complete Design with two factors. First factor was concentration ground coffee (10%, 30%), and the next one was concentration of sugar (80%, 90%, and 100%). The observation parameters included rendement, moisture content, ash content, and sensory properties. The result was suspected that chemical properties did show significant effect and the best result from important attributed taste was shown by 30% ground coffee concentration and 100% sugar concentration.